ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PEMILIHAN KARIR SEBAGAI DOSEN BAGI MAHASISWA AKUNTANSI (STUDI PADA JURUSAN AKUNTANSI FE UNIVERSITAS BANGKA BELITUNG) - Wardhani, Rulyanti Susi; Lesmana, Ivan (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2013)
This study aims to determine the effect of intrinsic value of work, income, availabilityof work opportunities, work environment, sacrifice of profession, skills, and workunderstanding to career selection of accounting students being a lecturer. Primarydata is collected from the field. Samples are 119 students using Slovin formula andanalyzed by factor analysis.The analysis yields there are two factors affecting thecareer selection of accounting students being a lecturer. First, job informationconsisted of some variables such as income, availability of work opportunities, andwork understanding. Second, personality consisted of work intrinsic value and workenvironment. There is relation between those factors showed by the result ofanalisis factor in which the magnitude of both is high enough over 0.5 (50%). Theamount of the first factor is 65% and the second one is 57.9%. So, it can beconcluded that the most dominant factor is the first factor (job information).Keywords: intrinsic value of work, income, availability of work opportunities, workenvironment, sacrifice of profession. skills, work understanding,personality.